The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.2307/2667055
|View full text |Cite
|
Sign up to set email alerts
|

Provisional Selves: Experimenting with Image and Identity in Professional Adaptation

Abstract: This article describes how people adapt to new roles by experimenting with provisional selves that serve as trials for possible but not yet fully elaborated professional identities. Qualitative data collected from professionals in transition to more senior roles reveal that adaptation involves three basic tasks: (1) observing role models to identify potential identities, (2) experimenting with provisional selves, and (3) evaluating experiments against internal standards and external feedback. Choices within ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

61
1,876
4
70

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,839 publications
(2,101 citation statements)
references
References 35 publications
61
1,876
4
70
Order By: Relevance
“…These could help shed light on motivation and interests areas, components of talent that are not always visible to other parties. Because motivation and interests are approached as dynamically influenced by personal and environmental factors (Ibarra, 1999), we emphasize that talent-identification should be a continuous endeavor. Within this perspective life-long interventions for talent-identification are deemed suitable, not only early-career interventions as is so often the case in HR practice today (Savickas et al, 2009).…”
Section: Measuring Talentmentioning
confidence: 99%
“…These could help shed light on motivation and interests areas, components of talent that are not always visible to other parties. Because motivation and interests are approached as dynamically influenced by personal and environmental factors (Ibarra, 1999), we emphasize that talent-identification should be a continuous endeavor. Within this perspective life-long interventions for talent-identification are deemed suitable, not only early-career interventions as is so often the case in HR practice today (Savickas et al, 2009).…”
Section: Measuring Talentmentioning
confidence: 99%
“…These can be identities from social environments and settings quite foreign to their own, and they can include such elements as dress, narratives, or even religious practices (e.g., Creed and Scully 2000, Ibarra 1999, Meyerson 2003, Van Maanen 2001. For example, Meyerson (2003) describes how less powerful members in financial, hi-tech, and consumer products organizations quietly resisted the status quo by drawing on their alternative racial, sexual, or gender identities to dress differently, furnish their offices differently, and lead differently than those in the dominant group.…”
Section: Current Literature On Practice Challenge and Change By Less mentioning
confidence: 99%
“…Evidence has shown that these differences are directly related to the process of negotiating and overcoming identity conflict (e.g., Burke 1991Burke , 2003Ibarra 1999). As discussed earlier, because individuals generally have multiple identities (Ashforth et al 2000;Pratt and Forman 2000), identity conflict can occur when one identity's (e.g., parent) behavioral expectations go against another identity's (e.g., business owner) behavioral expectations.…”
Section: The First Step: Identity Foundationmentioning
confidence: 99%
“…Individuals seem to undertake a deeper analysis of a possible identity conjecture beyond the testing involved in thought trials by assessing their new identity using internal standards of self-beliefs (Ibarra 1999;Rafaeli and Sutton 1989) and external feedback based on other people's responses to their potential implementation of the new role (Ibarra and Petriglieri 2010;Meister et al 2014). These internal and external forms of feedback provide information about the match between the alternative identity and the role it corresponds to (Bandura 1977;.…”
Section: Discipline Following Open Identity Playmentioning
confidence: 99%